PS02.046: UNRAVELING TUMOR HETEROGENEITY OF ESOPHAGEAL ADENOCARCINOMA (EAC) THROUGH HIGH-THROUGHPUT OF SORTED TUMOR CELL POPULATIONS. (14th September 2018) - Bonora, Elena; Isidori, Federica; Bozzarelli, Isotta; Lugaresi, Marialuisa; Malvi, Deborah; Söderström, Henna; Bolognesi, Chiara; Forcato, Claudio; D'Errico, Antonietta; Fiocca, Roberto; Seri, Marco; Krishnadath, Kausilia; et al.
Abstract: Background: In EAC clinical, histological, immune-histochemical and genetic patterns were documented, which support the existence of biologically different sub populations. We studied genetic intra/inter tumor heterogeneity of EAC with a new technology based on sorting of specific cell populations. Methods: Formalin embedded material obtained from 16 EAC surgical specimens, classified according to the presence/absence of intestinal metaplasia in esophagus (BIM) and stomach (GIM) in BIM + GIM- (Barret's like), BIM-GIM- (cardio-pyloric like), BIM—GIM + (gastric like) types, was processed using a high-throughput cell sorting technology. Stromal and tumor cell populations were sorted based on antibodies against vimentin/pan-cytokeratin and on DNA content. Targeted resequencing on DNA extracted from the sorted cells was performed for 63 cancer-related genes (OncoSeek panel). Results: In 11/16 (68.75%) of cases a mutation in TP53 was detected, and in 2 we observed CDKN2A (TP53 regulator) mutations. In Barret's like and Gastric like sub types only mutations of TP53 or TP53regulator genes were present. In pyloric like type TP53 and/or other different mutations of whom 2 in HNF1A were detected (Figure 1). Conclusion: Selective sorting led to new patterns of EAC tumor mutational status and heterogeneity, among others somatic mutations in HNF1A not previously found. Parallel analysis of unsorted samples failed to detect these specific mutations. The cardio-pyloric like sub type contains mutational patterns different than those of Barret's and gastric like types. Further research on additional cases is necessary to confirm these findings. Disclosure: All authors have declared no conflicts of interest.